SCREENING FOR COMPLICATIONS OF DIABETES MELLITUS - Fatmah Yassen Alattas; Ahmed Yaseen Alattas; Aeshah Mohammed Sultan; Amal Mohammed Junadi; Rasha Saleh Alhawass; Fatimah Salman Ghazwani; Alhanouf Hassan Ahmad Sheddwi; Fatima Mofarh A Albarrati; Khalid Mohammed Almulhim; Fatimah Ali A Haddadi; Zahir Ahmad Alamir; Mohammed Mohsen Hussain Alezzudin; et al. (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Diabetes, a chronic condition characterized by high levels of blood sugar, is widely recognized as a predominant factor contributing to end-stage renal disease, visual impairment, and nontraumatic lower-limb amputations. it has been identified as a significant contributor to cardiovascular morbidity and mortality, with statistics indicating that it ranks as the 7th leading cause of death exclusively in the United States. The financial impact of diabetes in the US was staggering in 2012, surpassing a staggering two hundred billion dollars. A considerable portion of the disability and financial burden associated with diabetes can be directly attributed to the management of its chronic complications, which often require extensive and costly medical interventions. The multifaceted nature of diabetes underscores the urgent need for comprehensive strategies aimed at prevention, early detection, and effective management of this complex condition to alleviate its far-reaching health and economic consequences.